Research on Corpus of Learners of Spanish as a Foreign Language - Torrijos, Mónica Belda (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
The present article bridges the acquisition of second languages and corpus linguistics. The creation of a corpus for the analysis of the use of Spanish by foreigners is a central part of the research of Spanish as a foreign language. If we compare the investigations of corpus compilations written in Spanish with the compilations in English, we will observe that they are not so numerous. However, in recent years, a new interest has appeared and there is a substantial amount of written and oral information about Spanish as a foreign language.